ANALISIS LAPORAN KEUANGAN KOPERASI DITINJAU DARI SK MENKOP DAN UKM RI NO. 06/PER/DEP.6/IV/2016 GUNA MENINGKATKAN TINGKAT KESEHATAN KEUANGAN (STUDI KASUS PADA KOPERASI KREDIT SENTOSA PALEMBANG) - Nova Tri Astuti; Puspa Utami (Program Studi Perbankan Syariah, 2021)
The Palembang Sentosa Credit Cooperative is one of the cooperatives in the city of Palembang and has 1,525 members. Where during its development experienced ups and downs. In this thesis the author discusses how the level of cooperative financial performance and its development in 2016 and 2017 if assessed based on aspects guided by the Decree of the Minister of Cooperatives and SMEs RI No.06/Per/Dep.6/IV/2016 which consists of 7 aspects, namely aspects capital, productive asset quality aspect, management aspect, efficiency aspect, liquidity aspect, independence and growth aspect and cooperative identity aspect. As we know that financial statements are very important in making a decision. The results of the study after calculating the 7 aspects of financial performance assessment at the Sentosa Credit Cooperative (KOPDIT), it appears that the level of the Sentosa Credit Cooperative's financial performance in 2016 was in the fairly healthy predicate and in 2017 the Sentosa Credit Cooperative's financial performance level remained at the moderate predicate. healthy. For 2016 the score obtained was 72.55 and in 2017 the score decreased to 67.40. Thus, the development of the level of financial performance of the Sentosa Credit Cooperative in 2016-2017 decreased by 5.15% but was still in a fairly healthy predicate.